Methicillin-resistant Staphylococcus aureus in Southwest Finland: Changing strain types and antimicrobial resistance – methods for outbreak investigation - Silvola, Jaakko (fi=Turun yliopisto|en=University of Turku|, 2026)
Staphylococcus aureus is a gram-positive, coccus-shaped bacterial species. It is a major opportunistic pathogen of humans and typically associated with purulent skin and soft tissue infections and invasive infections. It is asymptomatically carried by some third of the population in the anterior nares, skin or mucosa. Methicillin-resistant S. aureus (MRSA) is a strain with acquired broad-spectrum resistance to most β-lactams, key antibiotics in the treatment of staphylococcal infection. Treatment of MRSA infections is hence challenging. Combined with an effective asymptomatic transmission in healthcare institutions and the community, MRSA inflicts a long-lasting and significant burden on healthcare systems and human health worldwide. The aim of this thesis was to characterize transmission and risk factors of MRSA isolates exhibiting spa t172, reported as the most prevalent strain type during a period of increasing notification rate in Southwest Finland, 2007–2016 (Study I). We also aimed to analyse the changes in the antimicrobial susceptibility pattern of all MRSA isolates detected during the same period (Study II). Lastly, we aimed to evaluate the performance of a novel rapid bacterial strain typing tool, Fourier Transform Infrared Spectroscopy (FTIR) for outbreak detection and typing of S. aureus isolates, 2023– 2024 (Study III). Using whole-genome sequencing, we identified multiple clusters among the spa t172 isolates. Clusters of t172 were detected from healthcare and community sources in epidemiologically unlinked individuals, with identification dates spanning multiple years (Study I). During 2007–2016, the increase of MRSA notification rate was accompanied by an increasing trend of multi-resistant strains, driven by increases in resistance to erythromycin, clindamycin and tetracycline - and associated with community-acquisition, immigration and hospital care abroad (Study II). With the FTIR method we were able to detect multiple phenotypic subtypes of S. aureus sharing the same spa type, while the MRSA and MSSA isolates overall exhibited a high degree of phenotypic similarity (Study III). In conclusion, the assessment and adaptation of new laboratory-based analyses together with epidemiological investigation are crucial to limit the health impact of MRSA. Research of the MRSA transmission dynamics and changing pattern of antimicrobial resistance can provide information for targeted, local infection control measures and updated treatment guidelines.